The Achilles' heel of iron-based catalysts during oxygen reduction in an acidic medium. Issue 11 (15th October 2018) - Choi, Chang Hyuck; Lim, Hyung-Kyu; Chung, Min Wook; Chon, Gajeon; Ranjbar Sahraie, Nastaran; Altin, Abdulrahman; Sougrati, Moulay-Tahar; Stievano, Lorenzo; Oh, Hyun Seok; Park, Eun Soo; Luo, Fang; Strasser, Peter; et al.
Abstract : Exposing Fe–N–C catalysts to H2 O2 -byproduct leaves their catalytic sites untouched but decreases the turnover frequency via oxidation of the carbon surface. Abstract : For catalysing dioxygen reduction, iron–nitrogen–carbon (Fe–N–C) materials are today the best candidates to replace platinum in proton-exchange membrane fuel cell (PEMFC) cathodes. Despite tremendous progress in their activity and site-structure understanding, improved durability is critically needed but challenged by insufficient understanding of their degradation mechanisms during operation. Here, we show that FeN x C y moieties in a representative Fe–N–C catalyst are structurally stable but electrochemically unstable when exposed in an acidic medium to H2 O2, the main oxygen reduction reaction (ORR) byproduct. We reveal that exposure to H2 O2 leaves iron-based catalytic sites untouched but decreases their turnover frequency (TOF) via oxidation of the carbon surface, leading to weakened O2 -binding on iron-based sites. Their TOF is recovered upon electrochemical reduction of the carbon surface, demonstrating the proposed deactivation mechanism. Our results reveal for the first time a hitherto unsuspected key deactivation mechanism during the ORR in an acidic medium. This study identifies the N-doped carbon surface as the Achilles' heel during ORR catalysis in PEMFCs. Observed in acidic but not in alkaline electrolytes, these insights suggest that durable Fe–N–C catalysts are within reach for PEMFCs if rational strategies minimizing the amount of H2 O2 or reactive oxygen species (ROS) produced during the ORR are developed.